2007
DOI: 10.1038/nmat2033
|View full text |Cite
|
Sign up to set email alerts
|

Negative refraction in semiconductor metamaterials

Abstract: An optical metamaterial is a composite in which subwavelength features, rather than the constituent materials, control the macroscopic electromagnetic properties of the material. Recently, properly designed metamaterials have garnered much interest because of their unusual interaction with electromagnetic waves. Whereas nature seems to have limits on the type of materials that exist, newly invented metamaterials are not bound by such constraints. These newly accessible electromagnetic properties make these mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
663
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 804 publications
(682 citation statements)
references
References 15 publications
16
663
0
3
Order By: Relevance
“…Lasing [1][2][3] , superconducting microwave properties 4,5 , negative refraction 6,7 and stimulated phonon emission ('sasing') 8,9 all require some degree of coherence in the EM phases across layers. Phasesensitive electric fields have been measured for short light pulses in ionized gases 10 ; interferometric (wave mixing) techniques have been used to resolve the complex polarizationP of near bandedge absorption in single semiconductor quantum wells or thick films 11 .…”
mentioning
confidence: 99%
“…Lasing [1][2][3] , superconducting microwave properties 4,5 , negative refraction 6,7 and stimulated phonon emission ('sasing') 8,9 all require some degree of coherence in the EM phases across layers. Phasesensitive electric fields have been measured for short light pulses in ionized gases 10 ; interferometric (wave mixing) techniques have been used to resolve the complex polarizationP of near bandedge absorption in single semiconductor quantum wells or thick films 11 .…”
mentioning
confidence: 99%
“…Metal-based NIMs 3-11 have been actively studied because of their unusual physical properties and their potential for use in many technological applications [12][13][14][15][16][17][18][19][20][21][22] ; however, they usually have the disadvantage of demonstrating large optical losses in their metallic components. As an alternative to metal-based NIMs, dielectricbased photonic crystals (PhCs) have been investigated and shown to emulate the basic physical properties of NIMs [23][24][25][26][27] , while also having relatively small absorption losses at optical frequencies.…”
mentioning
confidence: 99%
“…Such materials were carefully studied by different groups [51][52][53][54][55][56][57][58][59][60][61][62][63]. It is shown that indefinite media can have negative group refraction, backward-wave effect, and partial focusing.…”
Section: The Methods To Reduce the Losses Of Optical Metamaterialsmentioning
confidence: 99%
“…But the double resonance scheme also causes large resonance losses and technical difficulties in design and fabrication. In addition to negative index materials, both theoretical and experimental studies show the properties of negative refraction and subwavelength imaging can also occur in some uniaxially anisotropic media, which can have lower losses and be easier to fabricate [51][52][53][54][55][56][57][58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation